Topical Propranolol Improves Epistaxis Control in Hereditary Hemorrhagic Telangiectasia (HHT): A Randomized Double-Blind Placebo-Controlled Trial - Mei-Zahav, Meir; Gendler, Yulia; Bruckheimer, Elchanan; Prais, Dario; Birk, Einat; Watad, Muhamad; Goldschmidt, Neta; Soudry, Ethan (Journal of clinical medicine, 2020)
Epistaxis is a common debilitating manifestation in hereditary hemorrhagic telangiectasia (HHT), due to mucocutaneous telangiectases. The epistaxis can be difficult to control despite available treatments. Dysregulated angiogenesis has been shown to be associated with telangiectases formation. Topical propranolol has demonstrated antiangiogenic properties. We performed a two-phase study, i.e., a double-blind placebo-controlled phase, followed by an open-label phase. The aim of the study was assessment of safety and efficacy of nasal propranolol gel in HHT-related epistaxis. Twenty participants with moderate-severe HHT-related epistaxis were randomized to eight weeks of propranolol gel 1.5%, or placebo 0.5 cc, applied to each nostril twice daily; and continued propranolol for eight weeks in an open-label study. For the propranolol group, the epistaxis severity score (ESS) improved significantly (−2.03 ± 1.7 as compared with −0.35 ± 0.68 for the placebo group, p = 0.009); hemoglobin levels improved significantly (10.5 ± 2.6 to 11.4 ± 2.02 g/dL, p = 0.009); and intravenous iron and blood transfusion requirement decreased. The change in nasal endoscopy findings was not significant. During the open-label period, the ESS score improved significantly in the former placebo group (−1.99 ± 1.41, p = 0.005). The most common adverse event was nasal mucosa burning sensation. No cardiovascular events were reported. Our results suggest that topical propranolol gel is safe and effective in HHT-related epistaxis.